About the Rhetoric Approach to the Philosophy Discourse Analysis - Мельникова, И. А. (Kalbotyra, 1997)
The article deals with philosophy discourse problem. The new rhetoric of Chaim Perelman is suggested as a method of philosophy discourse analysis. The potential abilities of the method are shown on L. Karsavin’s “The Principles of Policy”.